Pattern of arterial involvement of the head, neck, and eyes in giant cell arteritis: three case reports. Issue 6 (June 1991) - Butt, Z; Cullen, J F; Mutlukan, E
Abstract : The findings of two post-mortem examinations and one CT scan of patients with biopsy proved giant cell arteritis (GCA) are presented. The presence or absence of intracranial involvement in GCA is discussed.